La diplomacia de Smart Cities: el caso de la ciudad de Barcelona - Cerqueira, Olga María; Piqué, Josep Miquel; Miralles, Francesc (Universidad Nacional Autónoma de México, 2019)
This research is based on the diplomacy of Barcelona City and the configuration of a hegemonic discourse on Smart City, with repercussions at a local and global level. The emphasis is on interactions and coalitions in network with other cities, establishing that Barcelona, as Smart City, projects an image of a leading and dynamic city, under construction and continuous growth that exerts a relational leadership, besides aims conformation of networks and structures where cities and their actors are connected learning and exchanging experience, reaching international positioning, economic activity, and agreements, as a reflection of a narrative sustained in openness, flexibility and inclusion, that precisely justifies the participation and political action of Barcelona as a city in global multilevel governance.

El trabajo se fundamenta en torno a la diplomacia de la ciudad de Barcelona y a la configuración de un discurso hegemónico sobre Smart City, con repercusiones a nivel local y global. El énfasis se hace en relación con las interacciones y coaliciones en red con otras ciudades, se establece que Barcelona, como Smart City, proyecta una imagen de ciudad líder, dinámica, en construcción y crecimiento continuo, que ejerce un liderazgo relacional y apunta a la conformación de redes y estructuras donde las ciudades y sus actores están conectados al aprendizaje e intercambio de experiencia, al posicionamiento internacional, a la actividad económica y a la concreción de acuerdos como reflejo de una narrativa sostenida en la apertura, la flexibilidad y la inclusión.
Keywords: City; Diplomacy; Smart City; Ciudad; Diplomacia; Discourse; Smart City; Hegemony; Discurso; Hegemonía; International relations; Relaciones internacionales; https://purl.org/pe-repo/ocde/ford#5.02.04